Optimizing Islamic Religious Colleges In Facing The Era of Globalization - Dian, Dian; Indayanti, Aneu Nandya; Irfan Fanani, Asep; Nurhayati, Elis (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study examines the role of state Islamic tertiary institutions in responding to the challenges of globalization in Indonesia. One tertiary institution was used as a research case study, UIN Sunan Gunung Djati Bandung. This study uses qualitative methods through literature data collection, field observations, and interviews. The results of the research show that UIN Bandung has designed and prepared a strategy for facing the globalization era, which consists of seven main methods, which include: financial planning and allocation management; improvement of research and publication programs; lecture management; improvement and empowerment of international standard human resources; increasing global insight by maintaining Islamic scientific values; pilot projects for international class programs; and development of the quality of study programs. The seven strategies are supported by the initiative of the academic community independently so that it has succeeded in realizing UIN Bandung as one of the PTKI, which is ready to welcome the era of globalization and gain an international reputation.